Early postsurgical visualization of composite mesh used in ventral hernia repair by amide proton transfer MRI. Issue 1 (19th February 2013) - Franconi, Florence; Roux, Jérome; Garric, Xavier; Lemaire, Laurent
<x xml:space="preserve">Abstract</x> Purpose The feasibility of noninvasive visualization of composite meshes used in ventral hernia repair by amide‐proton transfer magnetic resonance imaging (APT‐MRI) was explored. Methods Magnetization transfer asymmetry ratio images of composite meshes were obtained in vitro and in vivo from fast‐spin echo acquisitions with frequency saturation offsets of ±3.5 ppm with respect to water frequency and no saturation. Three rats were assessed with APT‐MRI each week for 1 month after the intraperitoneal implantation of two meshes, one on each side of the incision. One mesh was coated with collagen and the other was not. Results In vitro, meshes were delineated with APT‐MRI as a thin continuous linear hypersignal located on one side of the mesh. Unlike collagen‐free meshes, collagen‐coated meshes were easily identified in vivo with APT‐MRI during the first 3 weeks postimplantation. The composite meshes magnetization transfer asymmetry ratio (8.7 ± 2.8%) were significantly different from the muscle magnetization transfer asymmetry ratio value (−0.9 ± 1.6%). After a month, the mesh value dropped down to 1.1 ± 3.9%. Muscle and mesh magnetization transfer asymmetry ratio values were not significantly different and mesh conspicuity was no longer possible. Conclusion The results suggest that APT‐MRI is a promising technique for noninvasive, early postsurgical visualization of composite meshes used in ventral hernia repair. Magn Reson Med 71:313–317, 2014. © 2013 Wiley Periodicals, Inc.